A qualitative analysis of radiography students' reflective essays regarding their experience of clinical placement during the COVID-19 pandemic. Issue 2 (March 2023) - O'Connor, M.; Lunney, A.; Kearney, D.; Murphy, S.
Abstract: Background: The COVID-19 pandemic significantly impacted healthcare services and clinical placement for healthcare students. There is a paucity of qualitative research into radiography students' experiences of clinical placement during the pandemic. Method: Students in stages three and four of a 4-year BSc Radiography degree in Ireland wrote reflective essays regarding their experience of clinical placement during the COVID-19 healthcare crisis. Permission was granted by 108 radiography students and recent graduates for their reflections to be analysed as part of this study. A thematic approach to data analysis was used, allowing themes to emerge from the reflective essays. Two researchers independently coded each reflective essay using the Braun and Clarke model. Results: Four themes were highlighted; 1) Challenges associated with undertaking clinical placement during the pandemic, such as reduced patient throughput and PPE-related communication barriers; 2) Benefits of clinical placement during the pandemic, in terms of personal and professional development and completing degree requirements to graduate without delay; 3) Emotional impact and 4) Supporting students in clinical practice. Students recognised their resilience and felt proud of their contribution during this healthcare crisis but feared transmitting COVID-19 to family. Educational and emotional support provided by tutors, clinical staff and the university was deemed essential by students during this placement. Conclusions: Despite the pressure hospitals were under during the pandemic, students had positive clinical placement experiences and perceived these experiences to have contributed to their professional and personal growth. Implications for practice: This study supports the argument for clinical placements to continue throughout healthcare crisis periods, albeit with additional learning and emotional support in place. Clinical placement experiences during the pandemic prompted a deep sense of pride amongst radiography students in their profession and contributed to the development of professional identity.